Socio-Economic Dimensions of Growth: An Analysis of Poverty Reduction and Inequality in Haryana (1993-94 To 2011-12). - Mittal, Nidhi (2014)
This study contributes to the ongoing debate on how the growth experienced by Haryana in the recent years is impacting poverty and income distribution and investigates whether the higher economic growth in the post-reform period trickled down to favour the poor or is biased against the poor and whether it is accompanied by increased income inequality? In this context, the study attempts to analyse and understand the dynamics of growth process in Haryana, its NSS regions and social groups for the period 1993-94 and 2011-12 using NSSO consumption expenditure surveys and the poverty lines as per the Tendulkar Committee recommendations. The study finds that there has been an increase in the growth rates of average per capita expenditure in the post-reform period; however, this growth has not been uniform across NSS regions, sectors and social groups. Moreover, there has been a decline in the incidence of poverty in all regions, social groups and across rural and urban areas. Further, inequality has decreased in overall Haryana with a sharp fall in Gini coefficients in rural Haryana contributed by decreasing inequalities among all social groups in rural Eastern Haryana.